Given the system of equations below, find x + y + z .
x 4 + y 1 + z 1 = 5
x 1 + y 1 − z 1 = 4
x 6 − y 1 − z 1 = 9
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Shorter solution if you add equations 1 & 3 first.
Problem Loading...
Note Loading...
Set Loading...
let a = x 1 ; b = y 1 ; c = z 1
x 4 + y 1 + z 1 = 5 becomes 4 a + b + c = 5 (equation 1)
x 1 + y 1 − z 1 = 4 becomes a + b − c = 4 (equation 2)
x 6 − y 1 − z 1 = 9 becomes 6 a − b − c = 9 (equation 3)
Subtract equation 2 from equation 1 to eliminate b . We obtain
3 a + 2 c = 1 (equation 4)
Add equation 2 and equation 3 to eliminate b. We obtain
7 a − 2 c = 1 3 (equation 5)
Add equations 4 and 5 to eliminate c. We obtain
1 0 a = 1 4
a = 1 0 1 4 = 5 7
In equation 4, substitute a = 5 7 to solve for c . We obtain
3 a + 2 c = 1
3 ( 5 7 ) + 2 c = 1
c = − 5 8
In equation 1, substitute a = 5 7 and c = − 5 8 to solve for b .
4 a + b + c = 5
4 ( 5 7 + b − 5 8 = 5
b = 1
From here, we can now find the values of x , y and z .
x = 7 5 ; y = 1 and z = − 8 5
x + y + z = 7 5 + 1 − 8 5 = 5 6 6 1